Primary care practitioners' diagnostic action when the patient may have cancer: an exploratory vignette study in 20 European countries. Issue 10 (31st October 2020) - Harris, Michael; Brekke, Mette; Dinant, Geert-Jan; Esteva, Magdalena; Hoffman, Robert; Marzo-Castillejo, Mercè; Murchie, Peter; Neves, Ana Luísa; Smyrnakis, Emmanouil; Vedsted, Peter; Aubin-Auger, Isabelle; Azuri, Joseph; et al.
Abstract : Objectives: Cancer survival rates vary widely between European countries, with differences in timeliness of diagnosis thought to be one key reason. There is little evidence on the way in which different healthcare systems influence primary care practitioners' (PCPs) referral decisions in patients who could have cancer. This study aimed to explore PCPs' diagnostic actions (whether or not they perform a key diagnostic test and/or refer to a specialist) in patients with symptoms that could be due to cancer and how they vary across European countries. Design: A primary care survey. PCPs were given vignettes describing patients with symptoms that could indicate cancer and asked how they would manage these patients. The likelihood of taking immediate diagnostic action (a diagnostic test and/or referral) in the different participating countries was analysed. Comparisons between the likelihood of taking immediate diagnostic action and physician characteristics were calculated. Setting: Centres in 20 European countries with widely varying cancer survival rates. Participants: A total of 2086 PCPs answered the survey question, with a median of 72 PCPs per country. Results: PCPs' likelihood of immediate diagnostic action at the first consultation varied from 50% to 82% between countries. PCPs who were more experienced were more likely to take immediate diagnostic action than their peers. Conclusion: When given vignettes of patients with a low but significant possibility of cancer, more than half of PCPs across Europe would take diagnostic action, most often by ordering diagnostic tests. However, there are substantial between-country variations.